La narrativa de C. Salvador (a propòsit del recull «La carn també somnia») - Alonso, Vicent (Caplletra. Revista Internacional de Filologia, 2015)
This article examines Salvador’s ability as narrator through a textual analysis of five of his works of prose –two published before the war of 1936 and three left unpublished. Alonso perceives a certain narrative weakness as a consequence of Salvador’s scarce and generic knowledge of the requirements and methods of this genre.